The Impact of Customer Intensity in Firm Performance: Tech Capabilities as A Moderating Variable - Fegada, Alfateh; Veres, Zoltan (European Scientific Journal, ESJ, 2024)
Entrepreneurial marketing â€œEMâ€ is considered to be suitable for small businesses. However, since the perspective has shifted from product and sales to a market orientation, interest in the creation of customer value has grown and has been the subject of intense discussion. Thus, in this study, we aim to investigate and describe the significant relationship between Customer intensity â€œCIâ€ and firm performance â€œFPâ€ in SMEs operating in Khartoum-Sudan, by utilizing technological capabilities â€œTCPsâ€ as a moderating variable. The resource-based view â€œRBVâ€ provides the theoretical foundation for this study regarding the effect of CI on FP among TCPs. Regarding the study objective, we assumed the following hypothesis: H1: Customer intensity has a significant relationship with firm performance dimensions: {profitability, sustainability, and customer satisfaction}. H2: We assume that TCPs can positively moderate the relationship between CI and FP. Accordingly, this study is quantitative. Reliable with the purpose of this study. Furthermore, our study relied on the â€œPositivism philosophyâ€, a deductive approach to theory development. Therefore, overall, 255 responses were received from the community of SMEs in Khartoum. To analyze the data firstly the following principal component analysis PCA, Correlation, and Rotation matrix were utilized to test the appropriateness of the study structure â€œthe pre-modelâ€ and check the validity of the questionnaire items. secondly, we used structural equation modeling (SEM) Path analysis to analyze and examine the significant relationships between all variables. The analysis revealed that customer intensity has a positive effect on profitability (p = 0.000), Customer intensity has also a positive effect on customer satisfaction (p = 0.001). Unlike, customer intensity has negative effects on sustainability (p = 0.216). Finally, the results show that technological capabilities positively moderate the relationship between Customer intensity and profitability (p = 0.000), sustainability (p = 0.007), and customer satisfaction (p = 0.000). Anyhow, these results confirmed the partial support for the first hypothesis and full support for the second hypothesis.